Influence of public policy on small social enterprises : emerging research and opportunities - Maher, Chi, 1963- (Business Science Reference, 2017)
"This book examines UK public policy framework and how they influence small third sector social enterprises. It explains the contextual background of the third sector and discusses historic and academic perspectives on the development of the sector and the emergence of social enterprises in the UK and the initiatives to of legal framework, procurement, and funding policies"- Resumé vydavatel
Keywords: sociální podniky -- Velká Británie; hospodářská politika -- Velká Británie -- 21. století; social enterprises -- Great Britain; economic policy -- Great Britain -- 21st century; monografie; elektronické knihy; monographs; electronic books